تقييم تكيُّف طلبة الجامعة مع الدعم البيداغوجي عن طريق التعليم عن بعد في ظل جائحة كوفيد 19 - دراسة حالة بجامعة غرداية (مجلة الواحات للبحوث والدراسات, 2025)
This Study Aims To Assess The Extent Of Student Adaptation After The Transition To Distance Learning In Light Of University Closure, Due To Covid-19, Using The Descriptive Analytical Method, And Exploring Different Statistical Tools. The Study Started From The Understanding Of Instructions Made Up By The Ministry Of Higher Education To Cope With The Emergency Situation, And Then Conducted A Study Of A Sample Of Pedagogical Skills. The Applied Study Was Conducted On The Faculty Of Economics Students At Ghardaia University, Data Gathered From A Sample Of 100 Individuals Using An E-Questionnaire. The Results Showed That There Is A Willingness To Distance Learning, However Access To The Moodle Platform Requires A Huge Support. It Also Shows That There Are Material And Human Obstacles That Limit Student’s Interaction With The Activities Available On Different Platforms. Students Prefer Props That Have An Asynchronous Reaction. However, The Level Of Interaction Was Very Low, Varying Between Different Grades And Specialties. Key Words: Covid-19, Remote Teaching, University Students, Evaluation, Moodle.